Front Cover: Building proteomic tool boxes to monitor MHC class I and class II peptide. Issue 1 (January 2017) - Schumacher, Frances‐Rose; Delamarre, Lélia; Jhunjhunwala, Suchit; Modrusan, Zora; Phung, Qui T.; Elias, Joshua E.; Lill, Jennie R.
Abstract : DOI:10.1002/pmic.201600061 MHCI and MHCII peptides are presented on the surface of all nucleated cells in mammals and provide the immune system with a mechanism to recognize both intracellular and extracellular proteins. Over the past few decades' researchers have characterized MHC presented peptide sequences and their relative abundance on the cell surface of malignant, virally infected and "normal" cells. These insights have enabled the development of various T cell mediated therapeutic strategies and, allowed researchers to monitor fluctuations in MHCI and MHCII peptides in response to disease etiology and drug treatment. This review discusses these topics with a focus on profiling MHC presented peptides to aid T cell mediated biotherapeutic development. For more details, see the review by Frances‐Rose Schumacher et al. (https://doi.org/10.1002/pmic.201600061 ).